72.5k views
4 votes
What is the solution to the following system of equations? y = −x^2 − 5x − 4 y = −x^2 + 9x − 18

1 Answer

4 votes

Answer:

X=1 Y= -10

Explanation:


Y=-x^(2) -5x-4 equation 1 \\Y=-x^(2) + 9x-18 equation 2

using equation 1, we substitute in equation 2

We have


-x^(2) -5x-4 = -x^(2) + 9x-18\\-14x=-14\\x=1\\

so, we substitute the X value in equation2

we have>


y=-(1^(2))+ 9(1)-18)=-10\\y=-10

User Snote
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.